Internet connectivity disruption in VU (VU) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in VU. Data sourced from IODA.
Network Disruption Incident ID: VU-2026-0008. Severity: critical. Confidence: 65%